Integritas Mahasiswa STIPAK Malang dalam Mengikuti Kuliah Daring - Listio, Siani; Saputra, Hengki (DIDAKTIKOS: Jurnal Pendidikan Agama Kristen, 2023)
Based on the researchers' observations while attending online lectures, the researcher found that some students did not pay attention to the lecturer explaining, take a walk around , playing social media/games, doing other subject assignments , not having permission to turn off the camera, talking/discussing with the people around him when the lecturer explained, he was always late for zoom so the researchers decided to conduct a study entitled "Student Integrity of STIPAK Duta Harapan Malang Year 2018-2019 in Attending Online Lectures. Here are three main problem formulations that will be examined in depth in this study, namely STIPAK students' understanding of integrity, forms of integrity in online learning and how  students class of 2018-2019 realize self-integrity in online lectures. By examining these three things, the research objective is to find out the perception of integrity, forms of integrity and its embodiment of integrity in online lectures. This study uses a qualitative phenomenological approach, because researchers are trying to find the essence or meaning of the problems studied. To optimize the data, this study uses a triangulation data collection technique, the researcher assumes that they will find a clear answer from the existing problem formulation. After analyzing the data obtained from the informants, the researchers found that the integrity forms of STIPAK students class 2018-2019 were: 1) being responsible, 2) time discipline, 3) obeying existing rule. However, in reality not all STIPAK students from class 2018-2019 are able to apply this attitude of integrity. The manifestation of the integrity of STIPAK Duta Harapan Malang students for the 2018-2019 class in online lectures is as follows: first, being responsible for the coursework given by doing it honestly even without supervision from the lecturer. Apart from academic assignments, students also get used to being responsible in terms of leadership that has been entrusted from the campus and from lecturers. Second, time discipline. Students try to use their time as well as possible, one of which is during class hours, students force themselves to continue to consistently attend lectures until they are finished. Also try to get in on time. Third, comply with every rule that exists both from the campus and from the lecturers. The advice given to STIPAK Duta Harapan Malang students in taking online lectures is as follows: Because the lecture process is not directly supervised by lecturers or the campus, students need to get used to turning on the camera while attending online lectures. Students are given the opportunity to be more active in the lecture process such as discussions or questions and answers so that students can focus on attending lectures. With the demands given in the lecture process, there will be a sense of responsibility in students. The advice given to STIPAK Duta Harapan Malang students in taking online lectures is as follows: Because the lecture process is not directly supervised by lecturers or the campus, students need to get used to turning on the camera while attending online lectures. Students are given the opportunity to be more active in the lecture process such as discussions or questions and answers so that students can focus on attending lectures. With the demands given in the lecture process, there will be a sense of responsibility in students. Students need to be reminded again that they are prospective PAK teachers who teach about the truth of God's Word and serve as role models for students. Therefore, during the lecture process students must get used to having integrity in any case, especially in taking online lectures.